2013
DOI: 10.1016/j.neuro.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Mother's environmental tobacco smoke exposure during pregnancy and externalizing behavior problems in children

Abstract: Background While the impact of active maternal smoking during pregnancy on child health has been well investigated, the association between maternal passive smoking, or environmental tobacco smoke (ETS), or second-hand smoke, and behavioral development of offspring is less clear. This study examines the association between maternal ETS exposure during pregnancy and child behavior problems. Methods Cross-sectional data of 646 mother–child pairs from the Jintan China Cohort Study were used in the analyses. Mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 54 publications
(79 reference statements)
2
25
0
2
Order By: Relevance
“…Studies related to substance abuse found that pre-pregnancy risk drinking (Knudsen et al 2014) increased IEP, methamphetamine use during pregnancy increases IEP ) and EP (Twomey et al 2013), tobacco exposure during pregnancy (Liu et al 2013) and maternal smoking during child preschool years increases IEP (Paterson et al 2013). One study reported non-significant results to the effect of methamphetamine exposure during pregnancy in EP (Liles et al 2012).…”
Section: Substance Abusementioning
confidence: 99%
“…Studies related to substance abuse found that pre-pregnancy risk drinking (Knudsen et al 2014) increased IEP, methamphetamine use during pregnancy increases IEP ) and EP (Twomey et al 2013), tobacco exposure during pregnancy (Liu et al 2013) and maternal smoking during child preschool years increases IEP (Paterson et al 2013). One study reported non-significant results to the effect of methamphetamine exposure during pregnancy in EP (Liles et al 2012).…”
Section: Substance Abusementioning
confidence: 99%
“…The published literature on the role of tobacco is currently limited by the absence of any measures of secondhand smoke exposure to the mother during pregnancy. This is an important gap, given that (1) secondhand smoke is a different chemical mixture than primary smoke, (2) there is evidence that secondhand smoke exhibits neurodevelopmental toxicity, 61,62 and (3) it is a very common exposure. Given the complexity of tobacco mixtures and the biologic plausibility of impact, future studies should evaluate the role of secondhand exposure and consider biomarker measures of tobacco; these measures are objective, quantitative, and integrate all sources of exposure and, although not yet used in this literature due to the preponderance of retrospective designs, could be used when biologic materials have been stored or can be prospectively collected.…”
Section: Evidence Regarding Environmental Chemical Pollutantsmentioning
confidence: 99%
“…Pediatric SHSe has been shown to exacerbate asthma symptoms [1,2], and is associated with increased risk of bronchitis, pneumonia and other respiratory infections [3], sudden infant death syndrome [4,5], middle ear disease [6], atopic dermatitis [7], attention deficit hyperactivity disorder [8], externalizing behavior problems [9] and cognitive development delays [10,11]. Despite declines in US smoking prevalence, 50% of US children are routinely exposed to secondhand smoke [12], and over 30% of US children live in homes where a resident or visitor smokes [13].…”
Section: Introductionmentioning
confidence: 99%